2020
DOI: 10.1371/journal.pone.0234854
|View full text |Cite
|
Sign up to set email alerts
|

Early or delayed umbilical cord clamping? Experiences and perceptions of nurse-midwives and obstetricians at a regional referral hospital in Tanzania

Abstract: Background Umbilical cord clamping is a crucial step during the third stage of labour that separates the newborn from the placenta. Despite the available evidence that delayed umbilical cord clamping is more beneficial to infants, as well as the existence of 2014 WHO recommendation that the umbilical cord should be clamped between 1 and 3 minutes, its implementation is still low in many countries including Tanzania. Objective This study describes the experiences and perceptions of nurse-midwives'and obstetrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…A study in Tanzania showed that although the healthcare provider commonly practiced clamping the umbilical cord immediately after delivery, they were aware that delayed cord clamping has a potential benefit of oxygenation to the newborn in the event of the need for resuscitation. 25 Our study also shows that despite the education of healthcare providers on keeping the cord intact during resuscitation, two-thirds of the noncrying babies received resuscitation after cord clamping. There is a need to implement a delay in clamping as a quality improvement intervention to improve initial steps of resuscitation-especially stimulation and if necessary bag-and-mask ventilation.…”
Section: Discussionmentioning
confidence: 60%
“…A study in Tanzania showed that although the healthcare provider commonly practiced clamping the umbilical cord immediately after delivery, they were aware that delayed cord clamping has a potential benefit of oxygenation to the newborn in the event of the need for resuscitation. 25 Our study also shows that despite the education of healthcare providers on keeping the cord intact during resuscitation, two-thirds of the noncrying babies received resuscitation after cord clamping. There is a need to implement a delay in clamping as a quality improvement intervention to improve initial steps of resuscitation-especially stimulation and if necessary bag-and-mask ventilation.…”
Section: Discussionmentioning
confidence: 60%
“…Midwives' attitudes and perceptions of CCT were reported in six papers 11,33,40–42,45 . Expectant women's preferences were significant factors in the management of third‐stage labor and cord clamp timing 11,33,45 .…”
Section: Resultsmentioning
confidence: 99%
“…This search of international literature identified 18 eligible studies. Reference lists of selected articles were also examined for relevant publications, which met review inclusion criteria 11,14–16,32–45 . Empirical studies selected for this review used quantitative (n = 15) and qualitative designs (n = 3).…”
Section: Aims and Methodsmentioning
confidence: 99%
See 2 more Smart Citations